ALGORITMOS DE CÁLCULO PARA EL PROBLEMA DE DIFUSIÓN EN UNA MEZCLA GASEOSA DE TRES COMPONENTES - Armijo C., J. (2010)
We propose algorithms for calculating the diffusion problem in a gas mixture of three components. The algorithms are derived by solving the Maxwell-Stefan equation by Laplace transform. Molar flux are calculated and compared with those obtained from the Taylor-Krishna methodology. The results show that the net diffusion of chemical species in mixtures of more than two components can be set in the opposite direction to the gradient of concentration or may be zero even though the gradient is different from zero